Evaluating the biomechanical interaction between the medical compression stocking and human calf using a highly anatomical fidelity three-dimensional finite element model. Issue 11 (June 2021) - Lu, Yongtao; Zhang, Daxing; Cheng, Liangliang; Yang, Zhuoyue; Junyan Li,
The beneficial effects of the medical compression stocking (MCS) in the treatment of venous disorders of the human lower limb have been recognized. However, the effectiveness of the MCS on the internal tissues of the lower limb has not been properly evaluated. The aim of the present study was to shed light on the mechanism of compression therapy using a highly anatomical fidelity three-dimensional finite element (FE) model. A FE calf model of a 40-year-old female was created from magnetic resonance images, in which the bones, the muscle groups, three veins (the great saphenous vein, medial peroneal vein and small saphenous vein), the subcutaneous tissues (fascia) and the skin were reconstructed. The model was validated using experimental data collected in-house, and then the influence of different levels of external compression and the biomechanical effect of the MCS under the pathological conditions were investigated. The results showed that the pressure at the skin–stocking interface was largely influenced by the external compression pressure with an increase of up to 54.98%, while the pressure was neither influenced by the impairment of the muscular tissues nor by the impairment of the calf veins, with the largest change of just 5.63%. The trans-mural pressure was increased more by the impairment of the calf veins than by the impairment of the muscular tissues. The volume reductions in the calf veins were not evenly distributed. The present study provides some guidance on compression therapy.